PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR SISWA - Rahmad Alamsyah; Bambang Sahono (DIADIK, 2024)
This study aims to find out: (1) the application of the Snowball Throwing type cooperative learning model in increasing student learning participation in PPKN Subjects in Class XI MIPA (2) the application of the Snowball Throwing type cooperative learning model can increase Student Learning Achievement in PPKN Subjects in Class XI MIPA (3) the application of the Snowball Throwing type cooperative learning model to improve student Learning Achievement in PPKN Subjects in Class XI MIPA. This study used a Classroom Action Research (PTK) design and quasi-experimentation. The research subjects (PTK) were students of class XI MIPA.1 semester 1 as many as 34 people. For the quasi-experimental sample of class XI MIPA.2 students as many as 30 people and for the control class is class XI MIPA.3 as many as 30 people. The data collection technique in this study used observation sheets and tests. The results showed that (1) the application of the Snowball Throwing learning model can increase student learning participation in PPKN subjects at SMA Negeri 4 Lahat. Academic Year 2022/2023. (2) the application of the Snowball Throwing learning model model, can improve student learning achievement and become a motivation for students in following the subject matter (3) the Snowball Throwing learning model, effectively improves student learning achievement in PPKN subjects